Cu-incorporation by melt-spinning in n-type Bi2Te2.7Se0.3 alloys for low-temperature power generation. (1st July 2019) - Kim, Minyoung; Kim, Sang-il; Cho, Hyun-joon; Mun, Hyuna; Kim, Hyun-sik; Lim, Jae-Hong; Kim, Sung Wng; Lee, Kyu Hyoung
Abstract: Herein, we report the enhanced thermoelectric performance of Cu incorporated Bi2 Te2.7 Se0.3 prepared by melt spinning. The electronic transport properties were significantly improved by Cu incorporation due to the synergetic effect of carrier tuning, band modification, and electron-phonon transport control. The steady dimensionless thermoelectric figure of merit higher than 0.90 was achieved in the wide range of temperature range of 350–450 K for Cu0.008 Bi2 Te2.7 Se0.3, which is 30% enhancement in comparison with pristine Bi2 Te2.7 Se0.3 . This result can lead to high thermoelectric power generation efficiency 4.2% at Δ T = 180 K. Graphical abstract: Unlabelled Image